2019
DOI: 10.1007/s00167-019-05350-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid closed wedge high tibial osteotomy improves patellofemoral joint congruity compared with open wedge high tibial osteotomy

Abstract: Purpose To evaluate clinical outcomes and radiographic changes in patellofemoral (PF) joint congruity between open wedge high tibial osteotomy (OWHTO) and hybrid closed wedge HTO (HCWHTO). Methods From 2011 to 2013, 36 knees in 31 patients who underwent OWHTO and 21 knees in 17 patients who underwent HCWHTO were evaluated in this retrospective study with a minimum 5-year follow-up. Radiological outcomes including hip-knee-ankle angle (HKA), femoral patellar height index (FPHI), preoperative PF osteoarthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 44 publications
(132 reference statements)
1
46
0
3
Order By: Relevance
“…Patellar infera leads to an increase in patellofemoral contact pressure, anterior knee pain, and patellar locking and a decreased range of motion. These changes eventually lead to the progression of patellofemoral joint OA [ 3 , 16 , 17 ]. Kim et al [ 8 ] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patellar infera leads to an increase in patellofemoral contact pressure, anterior knee pain, and patellar locking and a decreased range of motion. These changes eventually lead to the progression of patellofemoral joint OA [ 3 , 16 , 17 ]. Kim et al [ 8 ] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patellofemoral joint on the sagittal plane is also influenced by the operation [ 2 ]. Several studies have shown that OWHTO causes patellar infera, increases patellofemoral joint pressure pain, increases the risk of patellofemoral OA progression, and makes it more difficult for total knee arthroplasty to be performed in the future [ 3 8 ]. Kim et al [ 8 ] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not clear whether the postoperative changes observed in this study induce osteoarthritic progression of the patellofemoral joint, 10 , 11 it can be stated that correction of severe varus deformity by either DLO or isolated MOWHTO induces similar changes in the biomechanical environment of the patellofemoral joint. Since it has been reported that knees with severe varus deformity is generally combined with severe patellofemoral arthritis, 32 osteotomy procedures that exert less influence on the patellar position such as distal-tuberosity osteotomy, 33 , 34 closed wedge HTO, 8 , 28 and hybrid HTO 35 , 36 , 37 should be considered as alternative surgical options on the tibial side.…”
Section: Discussionmentioning
confidence: 99%
“…Patella infra leads to an increase in patellofemoral contact pressure, anterior knee pain, patellar locking and a decreased range of motion. These changes eventually lead to the progression of patellofemoral joint OA [3,16,17] . Kim et al [8] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the patellofemoral joint on the sagittal plane is also in uenced by the operation [2] . Several studies have shown that OWHTO causes patella infra, increases patellofemoral joint pressure pain, increases the risk of patellofemoral OA progression, and makes it more di cult for total knee arthroplasty to be performed in the future [3][4][5][6][7][8] . Kim et al [8] reported the prevalence of the progression of patellofemoral OA to be 41.2% in the femoral trochlea and 21.9% in the patella articular surface after more than 2 years in 114 patients who underwent OWHTO.…”
Section: Introductionmentioning
confidence: 99%